Vaccination of Children with recurrent and chronic inflammatory ENT pathology - M. P. Коstinov; A. A. Таrasova (Эпидемиология и вакцинопрофилактика)
Recommendations highlighted features vaccination of children with with recurrent and chronic inflammatory ENT pathology. It is shown how the immunization scheme may be changed according to the pathology and the age of the child.